Sustainable Competitive Advantage through Corporate Social Responsibility (CSR) and Green Behavior Strategies - Ahmed Abubakar; Shweta Belwal; Nuhu Mohammed; Umaru Danladi Mohammed (Discrete Dynamics in Nature and Society)
Driven by the pursuit of sustainable competitive advantage and consideration of the impact of corporate social responsibility activities on society and the need for environmentally friendly behaviors to improve companies’ sustainable performance, this study investigates the impact of corporate social responsibility (CSR) on firm performance through the use of green behavior. An empirical survey was carried out, data was collected from 176 respondents, constituting a 61.8% response rate of the sample of 278 employees, and the hypotheses derived from the literature review were tested using structural equation modeling. Firm performance was empirically found to be significantly impacted by both CSR and green behavior. Furthermore, the findings suggest that green behavior mediates the relationships between CSR and firm performance. By establishing the mediating role of green behavior, the study contributes to and expands the literature on firm performance and sustainable competitive advantage. Companies, thereby adopting green behavior, can enhance a firm’s performance and attain a sustainable competitive advantage.